2019
DOI: 10.1007/s00223-019-00622-0
|View full text |Cite
|
Sign up to set email alerts
|

Jumping Joints: The Complex Relationship Between Osteoarthritis and Jumping Mechanography

Abstract: We investigated the relationship between lower limb osteoarthritis (OA) and muscle strength and power (assessed by jumping mechanography) in UK community-dwelling older adults. We recruited 249 older adults (144 males, 105 females). OA was assessed clinically at the knee according to ACR criteria and radiographically, at the knee and hip, using Kellgren and Lawrence grading. Two-footed jumping tests were performed using a Leonardo Mechanography Ground Reaction Force Platform to assess maximum muscle force, pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…25 Mechanography is also increasingly used in the medical field with a focus on bone-related diseases. [26][27][28][29][30][31][32] Rittweger et al reported a strong correlation between mechanography and other time function assessment indices including walking speed, the "timed up & go test," and the "chair rising test" in adults. 21 There is a significant gender-dependent difference in the age-depending normative values at the age of 12 years and over.…”
Section: Introductionmentioning
confidence: 99%
“…25 Mechanography is also increasingly used in the medical field with a focus on bone-related diseases. [26][27][28][29][30][31][32] Rittweger et al reported a strong correlation between mechanography and other time function assessment indices including walking speed, the "timed up & go test," and the "chair rising test" in adults. 21 There is a significant gender-dependent difference in the age-depending normative values at the age of 12 years and over.…”
Section: Introductionmentioning
confidence: 99%